2012
DOI: 10.5120/5083-7333
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of Methods for Liver Tumor Classification from CT Datasets

Abstract: This paper proposes an automatic system for early detection of liver diseases from Computed tomography (CT) images. The general Computer Aided Diagnosis (CAD) system, including liver diagnosis can be done by segmenting a liver and lesion, extracting features and classify disease whether it is hepatoma or hemangioma. To segment a liver from CT abdominal images histogram analyzer and morphological operation is used. Then to extract a lesion from liver Fuzzy c-mean (FCM) clustering is used. In feature extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The number of features extracted varies based on positional difference values. The possible feature set extracted is 2, 5, 9, 14, 27, 44, 65 and 90, as (2,4), (4,2), (3,3), (0,7), (7,0), (6,1), (1,6), (2,5), (5,2), (3,4), (4,3), (0,8), (8,0), (1,7), (7,1), (2,6), (6,2), (3,5), (5,3), (4,4), (0,9), (9,0), (8,1), (1,8), (2,7), (7,2), (3,6), (6,3), (5,4), (4,5),(0,10), (10,0) , (1,9), (9,1), (2,8), …”
Section: Implementation and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of features extracted varies based on positional difference values. The possible feature set extracted is 2, 5, 9, 14, 27, 44, 65 and 90, as (2,4), (4,2), (3,3), (0,7), (7,0), (6,1), (1,6), (2,5), (5,2), (3,4), (4,3), (0,8), (8,0), (1,7), (7,1), (2,6), (6,2), (3,5), (5,3), (4,4), (0,9), (9,0), (8,1), (1,8), (2,7), (7,2), (3,6), (6,3), (5,4), (4,5),(0,10), (10,0) , (1,9), (9,1), (2,8), …”
Section: Implementation and Resultsmentioning
confidence: 99%
“…Kumar et al (2010Kumar et al ( , 2011Kumar et al ( , and 2012 reveals that curvelet transforms [7], [8], and [9] achieve better than wavelet transform for categorization. Mala et al (2010) and Gunasundari et al (2012) concluded that the performance of PNN is good when it is compared with other neural networks [10]. A classifier [11] consisting of three sequentially placed neural networks for four classes of hepatic tissues was developed.…”
Section: Past Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In feature extraction biorthogonal wavelet, Gray-level cooccurrence matrix and FDCT techniques are used [21]. The textual information obtained was used to train various neural networks such as BPN, PNN and Cascade feed forward BPN (CFBPN).…”
Section: Neural Networkmentioning
confidence: 99%
“…are used to train the SVM for classification. Mala et al [3] and Gunasundari and Anandhi [4] concluded that the performance of PNN is good when it is compared with other neural networks. Orthogonal moments [5] are used to classify the liver diseases from abdominal CT. Logistic maps and tent maps [6] are embedded in BPSO to find out the inertia weight of the BPSO.…”
Section: Introductionmentioning
confidence: 99%